HUBUNGAN DUKUNGAN SUAMI DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS RI SIDOMULYO PEKANBARU - Dwi Novita Sari; Nia Desriva; Fatma Nadia; Wira Ekdeni Aifa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Exclusive breastfeeding is an important effort to improve infants' health status and support their optimal growth and development. In 2024, the exclusive breastfeeding coverage in Pekanbaru City reached only 48.3% of the infants surveyed, indicating that the success rate of exclusive breastfeeding remains relatively low. The success of exclusive breastfeeding is influenced by various factors, one of which is husband’s support. Insufficient support from husbands may affect mothers' motivation and confidence to maintain exclusive breastfeeding until the infant reaches six months of age. This study aimed to analyze the relationship between husband’s support and exclusive breastfeeding in the working area of RI Sidomulyo Public Health Center, Pekanbaru. This study employed a quantitative research design with a cross-sectional approach. The study population consisted of all mothers with infants aged 0–6 months, totaling 67 participants. A total sampling technique was applied, making the entire population the research sample, with a total of 67 respondents. Data were collected using a structured questionnaire and analyzed through univariate and bivariate analyses using the Chi-Square test with a significance level of α = 0.05. The results showed that most respondents received good husband’s support (49.3%), while 52.2% of the mothers practiced exclusive breastfeeding. The bivariate analysis revealed a p-value of 0.018 (p < 0.05), indicating a statistically significant relationship between husband’s support and exclusive breastfeeding in the working area of RI Sidomulyo Public Health Center, Pekanbaru. It can be concluded that husband’s support is significantly associated with the success of exclusive breastfeeding. Therefore, husbands’ involvement in health education and health promotion programs should be enhanced to support the successful implementation of exclusive breastfeeding